Interrupted versus uninterrupted novel oral anticoagulant peri‐implantation of cardiac device: A single‐center randomized prospective pilot trial. Issue 11 (19th September 2018) - Ricciardi, Danilo; Creta, Antonio; Colaiori, Iginio; Scordino, Domenico; Ragni, Laura; Picarelli, Francesco; Calabrese, Vito; Providência, Rui; Ioannou, Adam; Di Sciascio, Germano
Abstract: Background: Many patients requiring cardiac implantable electronic device (CIED) implantation are on long‐term oral anticoagulant therapy. While continuation of warfarin has been shown to be safe and reduce bleeding complications compared to interruption of warfarin therapy and heparin bridging, it is not known which novel oral anticoagulants (NOAC) regimen (interrupted vs uninterrupted) is better in this setting. Methods: One‐hundred and one patients were randomized to receive CIED implantation with either interrupted or uninterrupted/continuous NOAC therapy before surgery. No heparin was used in either treatment arm. The primary end‐point was the presence of a clinically significant pocket hematoma after CIED implantation. The secondary end‐point was a composite of other major bleeding events, device‐related infection, thrombotic events, and device‐related admission length postdevice implantation. Results: Both treatment groups were equally balanced for baseline variables and concomitant medications. One clinically significant pocket hematoma occurred in the uninterrupted NOAC group and none in the interrupted group (P  =  0.320). There was no difference in other bleeding complications. No thrombotic events were observed in either of the two groups. Conclusions: Despite the paucity of bleeding events, data from this pilot study suggest that uninterrupted NOAC therapy for CIED implantation appears to be as safe as NOAC interruption and does not increase bleeding complications.